The Relationship Of Increasing Bmi On The Risk Of Cataracts - Rahmat Prayogi Niode; Ratih Nastasha Maharani; Ariyanie Nurtania (Jurnal EduHealth, 2024)
Cataract is a disorder of the eye where the pathological condition of the lens becomes cloudy due to hydration of lens fluid or denaturation of lens proteins, so that the view looks like it is covered in fog. This study aims to identify the relationship between increasing BMI and the risk of cataracts. The research was carried out by collecting secondary data from various research journal sources for 2018-2024. The research results show that changes in the eye lens can be influenced by body mass index. The body mass index that has a high influence on the occurrence of cataracts is obesity. The occurrence of cataracts in obesity is influenced by increased oxidative stress due to high leptin levels. Prevention that can be done to reduce the risk of clouding of the lens is by following a healthy diet and taking vitamin supplements. Another thing people can do is control their weight while maintaining a normal body mass index (18.5–25.0kg/m2).